(untitled) (Zaporizhzhia Historical Review, 2021)
The article is devoted to the analysis of the forms of the economic behavior of the owners of the household farms. During the scientific work the author allocates the number of the specific economic strategies on receiving and combination of the industrial resources, and also producing, distribution and the exchange of the agricultural products which allowed managing effectively within the framework of the house-hold farms. It is judged, that the specificity of the activity in their frameworks was caused by the antagonism between the economic interests of the state and the most of the population of Ukraine.